2019
DOI: 10.3389/fpsyg.2019.02035
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence, Self-Efficacy and Empathy as Predictors of Overall Self-Esteem in Nursing by Years of Experience

Abstract: Empirical research on self-esteem has a special interest in nursing professionals, because they work in a challenging environment that requires, in order to continue working during their working age, a strong physical, social and emotional involvement. The objective was to determine the explanatory value of individual variables such as Self-efficacy, Empathy and Emotional Intelligence on Self-esteem in a sample of nursing professionals, to identify which variables have the most explanatory value for overall se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 49 publications
8
22
0
5
Order By: Relevance
“…Emotional intelligence is gaining interest for its ability to promote the performance of high-level nursing by integrating nurses’ personal skills and patient-personal skills [ 42 , 43 ]. The results of this study are consistent with the studies of Pérez-Fuentes et al (2019) that the higher the emotional intelligence level, the lower the job stress and the higher the job-efficacy [ 44 ]. Lee and Seo (2015) argued that job-efficacy has an effect on areas such as positive outcome expectation and job satisfaction, and this helps to develop into a sense of satisfaction with overall life [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Emotional intelligence is gaining interest for its ability to promote the performance of high-level nursing by integrating nurses’ personal skills and patient-personal skills [ 42 , 43 ]. The results of this study are consistent with the studies of Pérez-Fuentes et al (2019) that the higher the emotional intelligence level, the lower the job stress and the higher the job-efficacy [ 44 ]. Lee and Seo (2015) argued that job-efficacy has an effect on areas such as positive outcome expectation and job satisfaction, and this helps to develop into a sense of satisfaction with overall life [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…[ 14 22 23 ] The EI self-expression dimension and subdimension assertiveness scores were significantly lower for new graduates compared to nurses in the other groups and suggested that a nurses' ability to effectively communicate their feelings increased with years of nursing experience. Findings were consistent with studies comparing EI and years of experiences of nursing groups[ 5 19 38 39 ] and consistent with the proposition that EI is a learned behavior and can improve over time. [ 10 11 ]…”
Section: Discussionsupporting
confidence: 86%
“…[ 14 19 26 28 39 ] Although this analysis used data used from a prior study,[ 24 ] findings were similar to recent nursing studies. [ 14 15 19 21 22 23 26 28 39 ] The collective findings could be used to inform the development of oncology-focused, supportive EI, and coping interventions to alleviate the ubiquitous OS that exists throughout the nursing workplace and in diverse cancer settings.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In our study, a positive and signi cant relationship was found between empathic tendency and professional self-esteem. The results of the study are similar to the literatüre [39][40][41]. The health sector needs healthcare professionals who can empathize in order to maintain a healthy patient-healthcare relationship, to approach the patient with understanding, to understand and feel their lives and feelings.…”
Section: Discussionsupporting
confidence: 64%